Pollen Dispersal and Pollination Patterns Studies in Pati Kopyor Coconut using Molecular Markers - Larekeng, Siti Halimah; Maskromo, Ismail; Purwito, Agus; Matjik, Nurhayati Anshori; Sudarsono, S. (International Coconut Community, 2015)
Parentage analysis has been used to evaluate pollen dispersal in Kopyor coconut (Cocos nucifera L.). Investigations were undertaken to elucidate (i) the dispersal of pollen, (ii) the rate of self and out-crossing pollination, and (iii) the distance of pollen travel in Pati kopyor coconut population. The finding of this activities should be beneficial to kopyor coconut farmers to increase their kopyor fruit harvest and to support breeding of this unique coconut mutant. As many as 84 progenies were harvested from 15 female parents. As many as 95 adults coconut provenances surrounding the female parents were analyses as the potential male parents for the progenies. The adult coconut palms were mapped according to their GPS position. All samples were genotyped using six SSR and four SNAP marker loci. Parentage analysis was done using CERVUS version 2.0 software. Results of the analysis indicated that evaluated markers were effective for assigning candidate male parents to all evaluated seedlings. There is no specific direction of donated pollen movement from assigned donor parents to the female ones. The donated pollens could come from assigned male parents in any directions relative to the female parent positions. Cross pollination occured in as many as 82.1% of the progenies analyzed. Outcrossing among tall by tall (TxT), dwarf by dwarf (DxD), hybrid by hybrid (HxH), TxD, DxT, TxH, DxH, and HxD were observed. Self-pollination (TxT and DxD) occurred in as many as 17.9% of the progenies. The dwarf coconut was not always self pollinated. The presence of DxD, TxD, and HxD outcrossing was also observed. The donated pollens could come from pollen donor in a range of at least 0-58 m apart from the evaluated female recipients. Therefore, in addition to the wind, insect pollinators may have played an important role in Kopyor coconut pollination.